Detection of left atrial thrombi by echocardiography. Issue 2 (February 1981) - Schweizer, P; Bardos, P; Erbel, R; Meyer, J; Merx, W; Messmer, B J; Effert, S
Abstract : A group of 111 patients with mitral valve disease was studied by M-mode and two-dimensional echocardiography. Five left atrial thrombi were demonstrated, two of which had probably been the source of previous embolic events. Two-dimensional echocardiography was superior to M-mode in providing spatial orientation. Using multiple cross-sections the exact localisation and the size of the thrombus formation could be estimated. Thrombus localisations at the upper, lateral, and septal atrial walls, normally inaccessible to the single-beam technique, were successfully imaged. Even two-dimensional echocardiography, however, constitutes an imperfect method. By comparison with the findings at surgery only one-third of confirmed thrombi could be detected non-invasively. According to their localisation seven clots in the appendage were missed by the ultrasound method. One further thrombus fixed to the upper left atrial wall near the entrance of the upper pulmonary veins was also undetected by echocardiography. Despite these limitations, the information provided by echocardiography can be most helpful in patient management. M-mode, in combination with two-dimensional echocardiography, is therefore recommended in all patients with mitral stenosis before diagnostic or therapeutic procedures are undertaken.